Student-patient interactional practices in a Malaysian Dental Faculty / Nursyahirah Saiful Maznan - Nursyahirah, Saiful Maznan (2018)
This study explores interactional practices of third-year dental students in Faculty of Dentistry, University Malaya (FoDUM) with their patients, and patients’ satisfaction in the engagement. It also aims to expand the growing literature on dental student-patient interaction and to enhance our understanding of doctor-patient interactions in localized and specialized site of engagement. 18 students and 10 patients participated in this study. Using a discourse analytical approach, this qualitative study incorporates Sarangi’s (2010) Activity Analysis on structural mapping to discover the structures involved in an accessible data type before injecting other relevant discourse and conversation tools to inspect the participants’ interactional practices during the entire engagement. Linguistic variations are found exhibited amongst the multilingual student-patient community in the setting as part of the practices in the setting. The study also reveals that the students are still confronting interactional challenges despite high satisfaction reported by all patients. The students’ needs and wants are also queried for to anticipate communicative issues in dental practices. One limitation of this study is its generalizability.